Preparation process of novel porous biphase calcium phosphate ceramic scaffold
By modifying the treatment of BCP precursor powder and introducing nano zinc oxide and coupling functional polymers, the problem of insufficient mechanical properties and biological activity of porous calcium phosphate ceramic scaffold material was solved, and a biphasic phase with high porosity and good penetration was prepared. Calcium phosphate ceramic scaffolds improve their applicability and biodegradability in bacterial environments.
Patent Information
- Application Number
- CN202411342014.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing porous calcium phosphate ceramic stent materials have problems such as poor mechanical properties, poor osteogenic activity, and insufficient single components and biological functions.
Using BCP precursor powder, sodium dodecyl sulfate, sodium carboxymethylcellulose and hydrogen peroxide, the modification process is carried out through microwave heating, gradient heating sintering and other processes to improve the porosity, penetration and biological of the ceramic scaffold. and nano zinc oxide and polymers with coupling functions are introduced to enhance antibacterial and mechanical properties.
A porous biphasic calcium phosphate ceramic stent with high porosity and good penetration was prepared, which improved the bioactivity and mechanical properties of the material, and significantly improved its applicability and biodegradability in bacterial environments.
Smart Images

Figure CN119191872A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic stents, in particular to a preparation process of a novel porous biphasic calcium phosphate ceramic stent. Background Art
[0002] The composition of biphasic calcium phosphate is similar to the inorganic substance of natural bone. Its properties such as degradability, absorption and high biological activity make it an ideal hard tissue replacement material. It is widely used in many fields such as bone replacement, drug sustained release, tissue engineering scaffolds, etc.
[0003] According to the pore-forming principle, the current preparation of porous calcium phosphate ceramics mainly includes three methods: adding pore-forming agents, organic foam impregnation and gas foaming. However, the current bioceramic scaffold materials still have problems such as poor mechanical properties, poor osteogenic activity, single composition and biological function. Summary of the invention
[0004] The purpose of the present invention is to provide a novel preparation process of a porous biphasic calcium phosphate ceramic scaffold to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A preparation process for a novel porous biphasic calcium phosphate ceramic scaffold comprises the following steps: mixing BCP precursor powder and sodium dodecyl sulfate, adding pure water and hydrogen peroxide and stirring, then adding a dispersant and sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold.
[0007] Furthermore, the raw material composition of the ceramic support is as follows, by weight: 8-12 parts of BCP precursor powder, 2-7 parts of sodium dodecyl sulfate, 0.1-0.8 parts of sodium carboxymethyl cellulose, 0-0.6 parts of dispersant, 3-10 parts of pure water, and 5-12 parts of hydrogen peroxide.
[0008] Furthermore, the working conditions of microwave heating are: microwave treatment at a power of 600 W for 0.5-3 min.
[0009] Furthermore, the working conditions for drying are: keeping warm at 50-100°C for 10-24h; the working conditions for gradient temperature sintering are: heating to 230-360°C and keeping warm for 0.5-2h, then heating to 1000-1500°C and keeping warm for 1-5h, and cooling to 200-300°C and keeping warm for 1-2h.
[0010] Furthermore, the preparation of BCP precursor powder includes the following steps: dissolving calcium nitrate in pure water, adjusting the pH to 7-12, adding a mixture of diammonium phosphate and pure water, stirring for 1-5 hours, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder.
[0011] Furthermore, the working conditions of aging are: temperature of 10-60°C, time of 12-24h; the working conditions of sintering are: temperature of 1100°C-1300°C, time of 1-6h.
[0012] Furthermore, the dispersant is one of sodium lauryl sulfate, polyoxyethylene lauryl ether, and sodium hexametaphosphate.
[0013] Further, the BCP precursor powder is modified to obtain a modified BCP precursor powder, and the preparation of the modified BCP precursor powder comprises the following steps:
[0014] 1) Mix zinc nitrate hexahydrate and deionized water, add BCP precursor powder, add a mixture of triethanolamine aqueous solution and anhydrous ethanol, stir for 1-2 hours, transfer to a reaction kettle, heat to 178-182° C. using a 600W microwave digester and keep warm for 15-20 minutes, cool, centrifuge, wash, dry, and grind to obtain a composite BCP precursor powder;
[0015] 2) N,N-dimethylformamide and composite BCP precursor powder are mixed, ultrasonically stirred for 1-2 hours, a mixed solution of styrene-maleic anhydride polymer with coupling function and deionized water is added, ultrasonically shaken for 10-20 minutes, centrifuged, and dried to obtain an intermediate preparation;
[0016] 3) The intermediate preparation and N-methylpyrrolidone are mixed, a linear polyetheramine is added, the temperature is raised to 178-182° C. and kept for 1-2 hours, deionized water is added, and the mixture is distilled under reduced pressure and dried to obtain a modified BCP precursor powder.
[0017] Further, the preparation of the styrene-maleic anhydride polymer having a coupling function comprises the following steps:
[0018] In a nitrogen atmosphere, maleic anhydride and toluene are mixed, the temperature is raised to 72-78°C, a mixed solution of azobisisobutyronitrile and toluene is added, a mixed solution of styrene, vinyltriethoxysilane and anhydrous ethanol is added, the temperature is kept for 30-40 minutes, the temperature is raised to 83-87°C and the temperature is kept for 50-70 minutes, cooled, filtered, washed and dried to obtain a styrene-maleic anhydride polymer with coupling function.
[0019] Further, the preparation of the linear polyetheramine comprises the following steps:
[0020] In a nitrogen atmosphere, N,N-dimethylethylenediamine and anhydrous ethanol are mixed, and a mixture of 1,4-butanediol diglycidyl ether and anhydrous ethanol is added in an ice bath, and the temperature is raised to 38-42°C and kept for 22-24 hours, and then rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a novel preparation process of a porous biphasic calcium phosphate ceramic scaffold. Through component and process design, a biphasic calcium phosphate ceramic scaffold with simple process, high porosity, good pore penetration, mass production and good biological activity is prepared.
[0023] In the present invention, by limiting the components, BCP precursor powder is used as a raw material, hydrogen peroxide is used as a foaming agent, sodium carboxymethyl cellulose is used as a rheological agent, and sodium dodecyl sulfate is used as a dispersant, and calcium phosphate ceramics with high porosity and good pore penetration are prepared without using a template.
[0024] In order to further improve the osteogenic inductivity and mechanical properties of ceramic scaffolds, the BCP precursor powder was modified. Zinc nitrate hexahydrate and triethanolamine were used as raw materials, and nano zinc oxide was in situ grown on the BCP precursor powder by microwave hydrothermal method to obtain composite BCP precursor powder, thereby improving the antibacterial property of the ceramic scaffold and enhancing the applicability of the material in a bacterial environment. Styrene-maleic anhydride polymer with coupling function was prepared by free radical polymerization of maleic anhydride, styrene and vinyltriethoxysilane, and then the composite BCP precursor powder was treated to obtain an intermediate preparation, in which the introduction of silicon element synergistically cooperated with zinc element to improve the biological activity of the material and promote bone tissue growth. The composite BCP precursor powder was surface modified to greatly increase the surface roughness and retention force.
[0025] In order to improve the uniformity of dispersion of BCP precursor powder in ceramic scaffolds and improve the uniformity of the properties of ceramic scaffolds, so that the purpose of uniform super dispersion can be achieved without the addition of additional super dispersants, the characteristics of polyether amines with excellent anchoring groups and reactivity are utilized. N,N-dimethylethylenediamine and 1,4-butanediol diglycidyl ether are used as raw materials to synthesize linear polyether amines with tertiary amines as anchoring groups. Then, the linear polyether amines are grafted with intermediate preparations to obtain modified BCP precursor powders, so that the BCP precursor powders have their own super dispersion, which greatly improves the various properties of the ceramic scaffolds. 附图说明
[0026] Figure 1 is a sintered picture of the porous dual-phase calcium phosphate ceramic prepared in Example 1;
[0027] Figure 2is a scanning electron microscope ×100 image of the porous dual-phase calcium phosphate ceramic prepared in Example 1;
[0028] Figure 3 is a scanning electron microscope ×250 image of the porous dual-phase calcium phosphate ceramic prepared in Example 1;
[0029] Figure 4 is a scanning electron microscope ×100 image of comparative example 1;
[0030] Figure 5 This is a scanning electron microscope ×250 image of Comparative Example 1. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0033] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0034] Example 1: A preparation process of a novel porous biphasic calcium phosphate ceramic scaffold, comprising the following steps: mixing BCP precursor powder and sodium dodecyl sulfate, adding pure water and hydrogen peroxide and stirring, then adding a dispersant and sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;
[0035] The raw material composition of the ceramic support is as follows: 9 parts of BCP precursor powder, 6 parts of sodium dodecyl sulfate, 0.3 parts of sodium carboxymethyl cellulose, 0.5 parts of dispersant, 6 parts of pure water, and 9 parts of hydrogen peroxide.
[0036] The working conditions of microwave heating were: 600 W microwave power for 3 min;
[0037] The working conditions for drying are: keeping at 80°C for 18 hours; the working conditions for gradient temperature sintering are: heating to 260°C for 1 hour, then heating to 1200°C for 1 hour, and cooling to 300°C for 1 hour.
[0038] The preparation of BCP precursor powder includes the following steps: dissolving 236.15 g of calcium nitrate in 1000 mL of pure water, adjusting the pH to 10, adding a mixture of 81.5 g of diammonium hydrogen phosphate and 617 mL of pure water, stirring for 3 h, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder;
[0039] The working conditions of aging are: temperature of 40° C., time of 18 h; the working conditions of sintering are: temperature of 1200° C., time of 3 h; the dispersant is sodium dodecyl sulfate.
[0040] Example 2: A preparation process of a novel porous biphasic calcium phosphate ceramic scaffold, comprising the following steps: mixing BCP precursor powder and sodium dodecyl sulfate, adding pure water and hydrogen peroxide and stirring, then adding sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;
[0041] The raw material composition of the ceramic support is as follows, by weight: 8 parts of BCP precursor powder, 2 parts of sodium dodecyl sulfate, 0.1 parts of sodium carboxymethyl cellulose, 3 parts of pure water, and 5 parts of hydrogen peroxide;
[0042] The working conditions of microwave heating were as follows: 600 W microwave power for 0.5 min;
[0043] The working conditions for drying are: keeping at 50°C for 24 hours; the working conditions for gradient temperature sintering are: heating to 230°C for 2 hours, then heating to 1000°C for 5 hours, and cooling to 200°C for 2 hours.
[0044] The preparation of BCP precursor powder includes the following steps: dissolving 236.15 g of calcium nitrate in 1000 mL of pure water, adjusting the pH to 7, adding a mixture of 81.5 g of diammonium hydrogen phosphate and 617 mL of pure water, stirring for 1 h, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder;
[0045] The working conditions for aging are: temperature 10°C, time 24h; the working conditions for sintering are: temperature 1100°C, time 6h;
[0046] The BCP precursor powder is subjected to modification treatment to obtain a modified BCP precursor powder, wherein the preparation of the modified BCP precursor powder comprises the following steps:
[0047] 1) 3 mmol of zinc nitrate hexahydrate and 100 mL of deionized water were mixed, 1.2 g of BCP precursor powder was added, and a mixture of 50 mL of 0.12 mol / L triethanolamine aqueous solution and 80 mL of anhydrous ethanol was added, stirred for 1 h, transferred to a reaction kettle, heated to 178 ° C with a 600 W microwave digester and kept warm for 20 min, cooled, centrifuged, washed, dried, and ground to obtain a composite BCP precursor powder;
[0048] 2) Mix 25 mL of N,N-dimethylformamide and 0.8 g of composite BCP precursor powder, stir ultrasonically for 1 h, add 1.4 g of styrene-maleic anhydride polymer with coupling function and 25 mL of deionized water, shake ultrasonically for 10 min, centrifuge, and dry to obtain an intermediate preparation;
[0049] 3) 8.1 g of the intermediate preparation and 12 mL of N-methylpyrrolidone were mixed, 3.6 g of linear polyetheramine was added, the temperature was raised to 178 ° C and kept for 2 h, 100 mL of deionized water was added, and the mixture was distilled under reduced pressure and dried for 12 h to obtain a modified BCP precursor powder;
[0050] The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps:
[0051] Under a nitrogen atmosphere, 2.5 g of maleic anhydride and 50 mL of toluene were mixed, the temperature was raised to 72° C., a mixed solution of 5 mg of azobisisobutyronitrile and 10 mL of toluene was added, and a mixed solution of 2.7 g of styrene, 0.1 g of vinyltriethoxysilane and 1.5 mL of anhydrous ethanol was added, the temperature was kept for 30 min, the temperature was raised to 83° C. and the temperature was kept for 50 min, cooled, filtered, washed and dried to obtain a styrene-maleic anhydride polymer with coupling function;
[0052] The preparation of linear polyetheramines comprises the following steps:
[0053] Under a nitrogen atmosphere, 3.6 g of N,N-dimethylethylenediamine and 10 mL of anhydrous ethanol were mixed, and a mixture of 7.2 g of 1,4-butanediol diglycidyl ether and 20 mL of anhydrous ethanol was added in an ice bath, and the temperature was raised to 38°C and kept warm for 24 h. The mixture was rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.
[0054] Example 3: A preparation process of a novel porous biphasic calcium phosphate ceramic scaffold, comprising the following steps: mixing BCP precursor powder and sodium dodecyl sulfate, adding pure water and hydrogen peroxide and stirring, then adding sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;
[0055] In parts by mass, the raw material composition of the ceramic support is: 9 parts of BCP precursor powder, 6 parts of sodium dodecyl sulfate, 0.3 parts of sodium carboxymethyl cellulose, 0.5 parts of dispersant, 6 parts of pure water, and 9 parts of hydrogen peroxide;
[0056] The working conditions of microwave heating were: 600 W microwave power for 3 min;
[0057] The working conditions for drying are: keeping at 80°C for 18 hours; the working conditions for gradient temperature sintering are: heating to 260°C for 1 hour, then heating to 1200°C for 1 hour, and cooling to 300°C for 1 hour.
[0058] The preparation of BCP precursor powder includes the following steps: dissolving 236.15g calcium nitrate in 1000mL pure water, adjusting the pH to 10, adding a mixture of 81.5g diammonium hydrogen phosphate and 617mL pure water, stirring for 3h, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder; the working conditions for aging are: temperature of 40°C and time of 18h; the working conditions for sintering are: temperature of 1200°C and time of 3h;
[0059] The BCP precursor powder is subjected to modification treatment to obtain a modified BCP precursor powder, wherein the preparation of the modified BCP precursor powder comprises the following steps:
[0060] 1) 3 mmol of zinc nitrate hexahydrate and 100 mL of deionized water were mixed, 1.2 g of BCP precursor powder was added, and a mixture of 50 mL of 0.12 mol / L triethanolamine aqueous solution and 80 mL of anhydrous ethanol was added, stirred for 1.5 h, transferred to a reaction kettle, heated to 180 ° C with a 600 W microwave digester and kept warm for 18 min, cooled, centrifuged, washed, dried, and ground to obtain a composite BCP precursor powder;
[0061] 2) Mix 25 mL of N,N-dimethylformamide and 0.8 g of composite BCP precursor powder, stir ultrasonically for 1.5 h, add 1.4 g of styrene-maleic anhydride polymer with coupling function and 25 mL of deionized water, shake ultrasonically for 15 min, centrifuge, and dry to obtain an intermediate preparation;
[0062] 3) 8.1 g of the intermediate preparation and 12 mL of N-methylpyrrolidone were mixed, 3.6 g of linear polyetheramine was added, the temperature was raised to 180° C. and kept for 1.5 h, 100 mL of deionized water was added, and the mixture was distilled under reduced pressure and dried for 12 h to obtain a modified BCP precursor powder;
[0063] The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps:
[0064] Under a nitrogen atmosphere, 2.5 g of maleic anhydride and 50 mL of toluene were mixed, the temperature was raised to 75° C., a mixed solution of 5 mg of azobisisobutyronitrile and 10 mL of toluene was added, and a mixed solution of 2.7 g of styrene, 0.1 g of vinyltriethoxysilane and 1.5 mL of anhydrous ethanol was added, and the mixture was kept warm for 35 min, and the temperature was raised to 85° C. and kept warm for 60 min, and the mixture was cooled, filtered, washed and dried to obtain a styrene-maleic anhydride polymer having a coupling function;
[0065] The preparation of linear polyetheramines comprises the following steps:
[0066] Under a nitrogen atmosphere, 3.6 g of N,N-dimethylethylenediamine and 10 mL of anhydrous ethanol were mixed, and a mixture of 7.2 g of 1,4-butanediol diglycidyl ether and 20 mL of anhydrous ethanol was added in an ice bath. The temperature was raised to 40°C and kept for 23 h. The mixture was rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.
[0067] Example 4: A preparation process for a novel porous biphasic calcium phosphate ceramic scaffold, comprising the following steps: mixing BCP precursor powder and sodium dodecyl sulfate, adding pure water and hydrogen peroxide and stirring, then adding sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;
[0068] The raw material composition of the ceramic support is as follows: 12 parts of BCP precursor powder, 7 parts of sodium dodecyl sulfate, 0.8 parts of sodium carboxymethyl cellulose, 10 parts of pure water, and 12 parts of hydrogen peroxide.
[0069] The working conditions of microwave heating were: 600 W microwave power for 1.5 min;
[0070] The working conditions for drying are: keeping at 100°C for 10 hours; the working conditions for gradient temperature sintering are: heating to 360°C for 0.5 hours, then heating to 1500°C for 1 hour, and cooling to 300°C for 1 hour.
[0071] The preparation of BCP precursor powder includes the following steps: dissolving 236.15 g of calcium nitrate in 1000 mL of pure water, adjusting the pH to 12, adding a mixture of 81.5 g of diammonium hydrogen phosphate and 617 mL of pure water, stirring for 5 h, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder;
[0072] The working conditions for aging are: temperature 60°C, time 12h; the working conditions for sintering are: temperature 1300°C, time 1h;
[0073] The BCP precursor powder is subjected to modification treatment to obtain a modified BCP precursor powder, wherein the preparation of the modified BCP precursor powder comprises the following steps:
[0074] 1) Mix 3 mmol of zinc nitrate hexahydrate and 100 mL of deionized water, add 1.2 g of BCP precursor powder, add a mixture of 50 mL of 0.12 mol / L triethanolamine aqueous solution and 80 mL of anhydrous ethanol, stir for 1-2 h, transfer to a reactor, heat to 182 ° C with a 600 W microwave digester and keep warm for 15 min, cool, centrifuge, wash, dry, and grind to obtain a composite BCP precursor powder;
[0075] 2) Mix 25 mL of N,N-dimethylformamide and 0.8 g of composite BCP precursor powder, stir ultrasonically for 2 h, add 1.4 g of styrene-maleic anhydride polymer with coupling function and 25 mL of deionized water, shake ultrasonically for 20 min, centrifuge, and dry to obtain an intermediate preparation;
[0076] 3) 8.1 g of the intermediate preparation and 12 mL of N-methylpyrrolidone were mixed, 3.6 g of linear polyetheramine was added, the temperature was raised to 182° C. and kept for 1 h, 100 mL of deionized water was added, and the mixture was distilled under reduced pressure and dried for 12 h to obtain a modified BCP precursor powder;
[0077] The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps:
[0078] In a nitrogen atmosphere, 2.5 g of maleic anhydride and 50 mL of toluene are mixed, the temperature is raised to 72-78° C., a mixed solution of 5 mg of azobisisobutyronitrile and 10 mL of toluene is added, and a mixed solution of 2.7 g of styrene, 0.1 g of vinyltriethoxysilane and 1.5 mL of anhydrous ethanol is added, the mixture is kept warm for 40 min, the temperature is raised to 87° C. and kept warm for 50 min, cooled, filtered, washed and dried to obtain a styrene-maleic anhydride polymer with coupling function;
[0079] The preparation of linear polyetheramines comprises the following steps:
[0080] Under a nitrogen atmosphere, 3.6 g of N,N-dimethylethylenediamine and 10 mL of anhydrous ethanol were mixed, and a mixture of 7.2 g of 1,4-butanediol diglycidyl ether and 20 mL of anhydrous ethanol was added in an ice bath, and the temperature was raised to 38°C and kept warm for 24 h. The mixture was rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.
[0081] Comparative Example 1: Commercially available calcium phosphate ceramics (Suzhou Dingan BCP ceramics, HA:TCP=70:30, 1-2 mm).
[0082] Comparative Example 2: Taking Example 3 as the control group, the styrene-maleic anhydride polymer with coupling function was replaced by styrene-maleic anhydride copolymer (Y47209: Shanghai Yuanye Biotechnology Co., Ltd.), and the other processes were normal.
[0083] Comparative Example 3: Example 3 was used as a control group, in which no linear polyetheramine was prepared, and other processes were normal.
[0084] Sources of raw materials used (for demonstration purposes only):
[0085] Maleic anhydride 108-31-6: Jinan Jinhao Chemical Co., Ltd.; sodium dodecyl sulfate S348686, sodium carboxymethyl cellulose C104984, diammonium hydrogen phosphate A112553, zinc nitrate hexahydrate Z111703, triethanolamine T108151, N,N-dimethylformamide D111999, N-methylpyrrolidone M119668, azobisisobutyronitrile A434183, styrene S110375, vinyltriethoxysilane T103647, N,N-dimethylethylenediamine D105347, 1,4-butanediol diglycidyl ether B109380: Aladdin reagent; hydrogen peroxide (mass concentration of 30%), calcium nitrate, anhydrous ethanol, toluene, analytical grade: Sinopharm Group reagent.
[0086] Performance test: The ceramic stents prepared in the embodiments and comparative examples were tested:
[0087] Porosity: mercury intrusion method was used for detection; biodegradability: the sample was placed in a sealed sample tube containing simulated body fluid SBF (CD090: Shanghai Aiyan Biotechnology Co., Ltd.), the sample mass to SBF volume ratio was 0.2g:1mL, kept at 37℃ for 7 days, SBF was replaced once a day, the wet weight of the immersed sample was measured, and the weight loss rate was calculated; the results are shown in Table 1;
[0088] Table 1
[0089]
[0090] The present invention provides a novel preparation process of a porous biphasic calcium phosphate ceramic scaffold. Through component and process design, a biphasic calcium phosphate ceramic scaffold with simple process, high porosity, good pore penetration, mass production and good biological activity is prepared.
[0091] according to Figure 2 , Figure 3 and Figure 4 , Figure 5 By comparison, it can be seen that the porosity and permeability of the porous biphasic calcium phosphate ceramic scaffold prepared by the present invention are higher than those on the market.
[0092] By comparing Example 3 with Comparative Example 2, it can be seen that in order to further improve the osteogenic inductivity and mechanical properties of the ceramic scaffold, the BCP precursor powder is modified, and zinc nitrate hexahydrate and triethanolamine are used as raw materials. Nano zinc oxide is in situ grown on the BCP precursor powder by a microwave hydrothermal method to obtain a composite BCP precursor powder, thereby improving the antibacterial property of the ceramic scaffold and enhancing the applicability of the material in a bacterial environment; maleic anhydride, styrene, and vinyltriethoxysilane are used for free radical polymerization to prepare a styrene-maleic anhydride polymer with a coupling function, and then the composite BCP precursor powder is treated to obtain an intermediate preparation, wherein the introduction of silicon element cooperates with zinc element to improve the biological activity of the material and promote bone tissue growth. The surface modification of the composite BCP precursor powder can increase the surface roughness and retention force, and greatly improve the mechanical properties of the ceramic scaffold.
[0093] By comparing Example 3 with Comparative Example 3, it can be seen that in order to improve the uniformity of dispersion of BCP precursor powder in the ceramic scaffold and improve the uniformity of the properties of the ceramic scaffold so that it can achieve the purpose of uniform super dispersion without the addition of a super dispersant, the polyether amine has excellent anchoring groups and reactive properties, and N, N-dimethylethylenediamine and 1,4-butanediol diglycidyl ether are used as raw materials to synthesize linear polyether amines with tertiary amines as anchoring groups. Then, the linear polyether amines are grafted with an intermediate preparation to obtain a modified BCP precursor powder, so that the BCP precursor powder has its own super dispersion, which greatly improves the various properties of the ceramic scaffold.
[0094] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A novel preparation process of a porous biphasic calcium phosphate ceramic scaffold, characterized in that: The following steps are involved: The BCP precursor powder and sodium dodecyl sulfate are mixed, pure water and hydrogen peroxide are added and stirred, and then a dispersant and sodium carboxymethyl cellulose are added, stirred, microwave heated, dried, gradient temperature sintered, and cooled to obtain a new porous biphasic calcium phosphate ceramic scaffold.
2. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The raw material composition of the ceramic support is as follows, by weight: 8-12 parts of BCP precursor powder, 2-7 parts of sodium dodecyl sulfate, 0.1-0.8 parts of sodium carboxymethyl cellulose, 0-0.6 parts of dispersant, 3-10 parts of pure water, and 5-12 parts of hydrogen peroxide.
3. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The working conditions of microwave heating are: microwave treatment at 600 W power for 0.5-3 min.
4. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The working conditions for drying are: keeping warm at 50-100°C for 10-24h; the working conditions for gradient temperature sintering are: heating to 230-360°C and keeping warm for 0.5-2h, then heating to 1000-1500°C and keeping warm for 1-5h, and cooling to 200-300°C and keeping warm for 1-2h.
5. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The preparation of BCP precursor powder includes the following steps: dissolving calcium nitrate in pure water, adjusting the pH to 7-12, adding a mixture of diammonium phosphate and pure water, stirring for 1-5 hours, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder.
6. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 5, characterized in that: The working conditions for aging are: temperature of 10-60°C, time of 12-24h; the working conditions for sintering are: temperature of 1100°C-1300°C, time of 1-6h.
7. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The dispersant is one of sodium lauryl sulfate, polyoxyethylene lauryl ether and sodium hexametaphosphate.
8. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The BCP precursor powder is subjected to modification treatment to obtain a modified BCP precursor powder, wherein the preparation of the modified BCP precursor powder comprises the following steps: 1) Mix zinc nitrate hexahydrate and deionized water, add BCP precursor powder, add a mixture of triethanolamine aqueous solution and anhydrous ethanol, stir for 1-2 hours, transfer to a reaction kettle, heat to 178-182° C. using a 600W microwave digester and keep warm for 15-20 minutes, cool, centrifuge, wash, dry, and grind to obtain a composite BCP precursor powder; 2) N,N-dimethylformamide and composite BCP precursor powder are mixed, ultrasonically stirred for 1-2 hours, a mixed solution of styrene-maleic anhydride polymer with coupling function and deionized water is added, ultrasonically shaken for 10-20 minutes, centrifuged, and dried to obtain an intermediate preparation; 3) The intermediate preparation and N-methylpyrrolidone are mixed, a linear polyetheramine is added, the temperature is raised to 178-182° C. and kept for 1-2 hours, deionized water is added, and the mixture is distilled under reduced pressure and dried to obtain a modified BCP precursor powder.
9. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 8, characterized in that: The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps: In a nitrogen atmosphere, maleic anhydride and toluene are mixed, the temperature is raised to 72-78°C, a mixed solution of azobisisobutyronitrile and toluene is added, a mixed solution of styrene, vinyltriethoxysilane and anhydrous ethanol is added, the temperature is kept for 30-40 minutes, the temperature is raised to 83-87°C and the temperature is kept for 50-70 minutes, cooled, filtered, washed and dried to obtain a styrene-maleic anhydride polymer with coupling function.
10. The preparation process of a novel porous biphasic calcium phosphate ceramic scaffold according to claim 8, characterized in that: The preparation of the linear polyetheramine comprises the following steps: In a nitrogen atmosphere, N,N-dimethylethylenediamine and anhydrous ethanol are mixed, and a mixture of 1,4-butanediol diglycidyl ether and anhydrous ethanol is added in an ice bath, and the temperature is raised to 38-42°C and kept for 22-24 hours, and then rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.
Citation Information
Patent Citations
Preparation method for calcium polyphosphate-tricalcium phosphate bone bracket
CN101716369A
Calcium phosphate / collagen composite biologic ceramic material and preparation method thereof
CN103055352A
Silicon / zinc ion doped biphase calcium phosphate ceramic scaffold and preparation method thereof
CN114767927A
High-strength composite material special for automobile structural parts and made of recycled nylon
CN115044200A
Production of porous ceramic sintered material
JP1991131580A
